Public Procurement Reform and Governance in Africa - Nyeck, S.N.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This book presents an interdisciplinary exploration of the governance of public procurement reform in Africa. Through a bottom-up approach to case studies and comparative analyses, scholars, practitioners, and social activists write about the organizational mechanisms and implementation gaps in public procurement governance in light of the general premises of national reform. Reforming the ways in which government purchases works, goods, and services from the private sector is one of the most sweeping policy reform undertaken in Africa in the past decade. Despite the transnational scope of policy change, very little is known about the mechanisms of public procurement governance at the subnational level. The argument in this volume is that policy reforms that mitigate contractual hazards along the three-dimensional "law-politics-business matrix" are more likely to bring about meaningful institutional transformation and broader social accountability. Key to substantive transformation of public procurement is the revitalization and professionalization of the public sector to meet the opportunities and challenges of development by contract.
Keywords: Africa-Politics and government; Public policy; Public administration; Comparative Politics; Public law; Development economics